"Silence as a Pragmatic Element and an Implicit Pattern in Discourse" - rhaaymi, youcef (El Omda in Linguistics and Discourse Analysis, 2018)
Through this paper, we aim to examine the phenomenon of silence and reveal its significance in the communicative process. Our effort comes within the framework of the growing attention in linguistic studies worldwide to issues of discourse and communication, particularly from a pragmatic perspective. In this article, we focus on silence as an implicit pattern in discourse that contributes to driving its flow and directing meaning according to contextual circumstances. This paper does not limit itself to interpreting the meanings of silence as a rhetorical device surpassing the rhetoric of speech—which many have observed—but rather seeks to trace the significance of silence, whether rhetorical or cognitive, intentional or forced. We confront silence as an expression of human essence and desire when the language of speech is absent.